Intuition: A potential life-raft for Philosophy and Theology?. Issue 5 (20th October 2022) - Howard, Jamie L.
ABSTRACT: The empirical turn has created an undercurrent of scrutiny regarding the relevance of disciplines such as philosophy and theology due to assumptions about the limitations of their epistemology. This article seeks to recognize that disciplines that are lauded as most relevant due to their reliance on empiricism as their main form of epistemology often rely upon intuition for making decisions in the research process. After delineating this process using Anthropological research as an example, I draw a parallel between descriptions of how intuition can be understood and used as a means of knowing in the work of Kant and several theologians with descriptions of how intuition is relied upon and necessarily emerges as a critical epistemology in the more traditionally empirically grounded discipline Anthropology. This parallel is offered as the launching place for connections between these disciplines through further examination of the use of intuition as an epistemology and hopes to equate the epistemo- logical integrity of disciplines such as philosophy and theology that admit to the use of intuition with those that are considered empiri- cal which rely upon intuition yet may not admit to its use overtly.